KLASIFIKASI BENTUK SHOURYAKUGO DALAM BAHASA JEPANG - Endah Noviastuti; Masilva Raynox Mael (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. This research aims to describe the classification of shouryakugo forms in printed media like newspaper and magazine. The form of words shortening in Japanese in newspapers and magazines became the main object in this research. The type of research is qualitative descriptive research. The object in this study is new words formed from the shortening process or shouryakugo contained in printed media such as The Daily Jakarta Shinbun newspaper and Nipponika magazine. The result of the research shows that there are total of 14 data of shouryakugo, of which 2 data is shortening at the beginning of word, 3 data of shortening in middle of word, 3 data of shortening at end of word, 5 data by removing partial word from word series, and 1 data shouryakugo by eliminating besides one word. Keywords: Classification, Forms, Shouryakugo